Basic House Sanitation in Swamp Banks in Pemulutan - Inoy Trisnaini; Imelda Gernauli Purba; Amrina Rosyada (Universitas Airlangga, 2021)
Introduction: Based on the health profile of Ogan Ilir District, in 2014. Pemulutan was the sub-district with the lowest number of households with clean and healthy living behaviour of all sub-districts in the Ogan Ilir Regency. Only 21.9% of households in Pemulutan had clean and healthy living behaviour, while the remaining 78.1% households did not have clean and healthy living behaviour. The purpose of this study was to assess the basic sanitation of houses in the swamp banks of Pemulutan. Methods: This research utilized a quantitative approach using a survey method. Research was conducted in five villages in Pemulutan with the cluster random sampling method. The samples in this study consisted of 140 households. Results and Discussion: It was found that 70.7% of respondents used rivers or swamps as clean water sources, even though 60% of the clean water sources used did not meet health requirements. Furthermore, 97.1% of defecation facilities did not meet health requirements, 89.3% used latrine did not meet health requirements, and 83.6% of sewerage did not meet health requirements. Conclusion: The basic sanitation conditions of the community houses in Pemulutan have not met health requirements. To overcome this, public knowledge and awareness of the role of home sanitation in supporting the health of family members should be increased, along with support from the local government